HARMONISASI HAK NEGARA DAN HAK INDIVIDU DALAM DALAM PENEGAKAN HUKUM - Siratni, Mia; Agustini, Sri (Ensiklopedia of Journal, 2025)
Abstract: Law enforcement is an important process that must reflect a balance between the state's right to maintain public peace and individual rights protected by law. This journal aims to analyze how the principle of balance is applied in the legal system in Indonesia, with a focus on the application of individual basic rights in the legal process. This research uses normative juridical methods with a statutory approach and case analysis to understand the application of these principles in practice. The research results show that although regulations in Indonesia have adhered to this principle of balance, their implementation still faces challenges, such as permits and weakening legal authorities' understanding of individual rights. The main recommendation from this research is the need to strengthen the capacity of law enforcement institutions and review legal policies that ignore individual rights.Keywords: Law Enforcement, State Rights, Individual Rights